2016
DOI: 10.2967/jnmt.115.169953
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing 18F-FDG Uptake Time Before Imaging Improves the Accuracy of PET/CT in Liver Lesions

Abstract: Beaumont Health System, Royal Oak, Michigan 18 F-FDG PET/CT has emerged as one of the fastest-growing imaging modalities. A shorter protocol results in a lower targetto-background ratio, which can increase the challenge of identifying mildly 18 F-FDG-avid lesions and differentiating inflammatory or physiologic activity from malignant activity. The purpose of this study was to determine the delay between radiotracer injection and imaging that optimizes target-to-background ratio while maintaining counts high en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Protocol deviations are quite common in clinical practice, a written survey among all Austrian PET/CT centers, showed that the average uptake time there was 55 minutes, with a range of 45 to 75 minutes, which is lower than in the EANM guidelines [65]. The optimal uptake time is as well tumor site specific, for liver imaging using 18 F-FDG PET the optimal uptake time was shown to be 90 minutes after FDG injection [66]. A possible reason for deviations in our study is that the radiopharmaceutical start time, extracted from the Digital Imaging and Communications in Medicine (DICOM) header, was not the time of FDG administration, as we assumed.…”
Section: Influence Of Pet Acquisition Timementioning
confidence: 93%
See 1 more Smart Citation
“…Protocol deviations are quite common in clinical practice, a written survey among all Austrian PET/CT centers, showed that the average uptake time there was 55 minutes, with a range of 45 to 75 minutes, which is lower than in the EANM guidelines [65]. The optimal uptake time is as well tumor site specific, for liver imaging using 18 F-FDG PET the optimal uptake time was shown to be 90 minutes after FDG injection [66]. A possible reason for deviations in our study is that the radiopharmaceutical start time, extracted from the Digital Imaging and Communications in Medicine (DICOM) header, was not the time of FDG administration, as we assumed.…”
Section: Influence Of Pet Acquisition Timementioning
confidence: 93%
“…Also, when comparing an exposure of 60 mA with 80 mA on the same scanner, or scanner 'B' with 'O', no trend indicating a dependency on bin width could be observed. In this case, the median number of stable features was 66.5 (55-70) and 67.5 (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72), respectively. Note that the total number of stable features was much lower when comparing different slice thicknesses.…”
mentioning
confidence: 85%